The Sandbox Revolution Raising Kids for a Just World. - Wylie-Kellermann, Lydia (Broadleaf Books, 2021)
It is a complex time to be a parent. Our climate is in crisis, economic inequality is deepening, and violence is escalating. How can parents cultivate in their children a love of the earth, a cry for justice, and a commitment to nonviolence? Written by parents who are also writers, teachers, organizers, artists, gardeners, and activists, The Sandbox Revolution offers a diversity of voices and experiences to guide us on a journey of justice-focused parenting.